Use of Native Lactococci as Vehicles for Delivery of DNA into Mammalian Epithelial Cells - Guimarães, Valéria Dellaretti (American Society for Microbiology, 2006)
The use of the food-grade bacterium Lactococcus lactis as a DNA delivery vehicle at the mucosal level is an attractive DNA vaccination strategy. Previous experiments showed that recombinant L. lactis expressing the Listeria monocytogenes inlA gene can deliver a functional gene into mammalian cells. Here, we explored the potential use of noninvasive L. lactis strains as a DNA delivery vehicle. We constructed two Escherichia coli-L. lactis shuttle plasmids, pLIG:BLG1 and pLIG:BLG2, containing a eukaryotic expression cassette with the cDNA of bovine β-lactoglobulin (BLG). The greatest BLG expression after transfection of Cos-7 cells was obtained with pLIG:BLG1, which was then used to transform L. lactis MG1363. The resulting L. lactis strain MG1363(pLIG:BLG1) was not able to express BLG. The potential of L. lactis as a DNA delivery vehicle was analyzed by detection of BLG in Caco-2 human colon carcinoma cells after 3 h of coincubation with (i) purified pLIG:BLG1, (ii) MG1363(pLIG:BLG1), (iii) a mix of MG1363(pLIG) and purified pLIG:BLG1, and (iv) MG1363. Both BLG cDNA and BLG expression were detected only in Caco-2 cells coincubated with MG1363(pLIG:BLG1). There was a decrease in the BLG cDNA level in Caco-2 cells between 24 and 48 h after coincubation. BLG expression by Caco-2 cells started at 24 h and increased between 24 and 72 h. BLG secretion by Caco-2 cells started 48 h after coincubation with MG1363(pLIG:BLG1). We conclude that lactococci can deliver BLG cDNA into mammalian epithelial cells, demonstrating their potential to deliver in vivo a DNA vaccine.